Performance characteristics of an air-cooled steam condenser incorporating a hybrid (dry/wet) dephlegmator - Heyns, Johan Adam (Stellenbosch : Stellenbosch University, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--Stellenbosch University, 2008.